UV-Spectrophotometric Determination of Dasatinib in Pharmaceutical Dosage Forms - Gowri Sankar, D.; Rajeswari, A.; Nagesh Babu, A.; Vamsi Krishna, M. (Asian Journal of Chemistry, 2010)
UV spectrophotometric method has been developed for the quantitative estimation of dasatinib in pure form as well as in pharmaceutical formulations. The drug exhibits absorption maximum at 330 nm in 0.1N HCl and obeys Beer's law in the concentration range of 2-10 μg/mL. The method was extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives.